Transverse colon volvulus and the wandering liver. (April 2023) - Morice, Donald; Stokes, Matthew A.R.; Douraghi-Zadeh, Dariush; Evans, Peter
Abstract: Introduction and importance: Transverse colon volvulus is a rare cause of colonic obstruction accounting for 1–3 % of colonic volvuli due to the short mesentery and hepatic and splenic attachments. Previous mobilisation of the flexures and conditions resulting in chronic dilatation of the colon predispose to the condition. The risk of mortality is high, ranging from 11 to 20 % highlighting the need for early diagnosis and intervention. Case presentation: We present a case of a 90-year-old male who was referred with a large bowel obstruction with a transition at the splenic flexure and the liver rotated to the left upper quadrant. The patient was taken to the theatre and an emergency laparotomy was performed with findings of a transverse colon volvulus. The liver was initially found in the left upper quadrant and was freely mobile in the upper abdomen consistent with an absence of the hepatic ligament. A subtotal colectomy was performed. Unfortunately, the postoperative course was complicated by a cardiac event and the patient died on postoperative day six. Clinical discussion: Absence of hepatic ligaments is a rare cause of transverse colon volvulus which has only been described in one previous case report. Diagnosis of transverse colon volvulus can be challenging and early operative intervention with colectomy is required to minimise mortality. Conclusion: This case illustrates an unusual cause of transverse colon volvulus secondary to the absence of the hepatic ligaments and stresses the need for early diagnosis and intervention due to the high mortality associated with this condition. Highlights: Transverse colon is a rare cause of large bowel obstruction but associated with a high mortality risk. Absence of the hepatic ligaments resulting in migration of the liver is a rare cause of transverse colon volvulus. Emergency colectomy is the recommended treatment.